2017
DOI: 10.1116/1.4990654
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of atmospheric pressure dielectric barrier discharge for inactivating airborne pathogens

Abstract: Ram P. (2017). Efficacy of atmospheric pressure dielectric barrier discharge for inactivating airborne pathogens. Journal of Vacuum Science and Technology A: Vacuum, Surfaces, and Films, 35(4) 041101. For guidance on citations see FAQs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 36 publications
(43 reference statements)
0
6
0
Order By: Relevance
“…Romero‐Mangado et al [ 19 ] studied the effect of DBD on aerosolized E. coli concluding that the cell structure is damaged to a varying extent and severe oxidation of the cell membrane is found, establishing effective inactivation of the bacteria. Romero‐Mangado et al [ 29 ] also demonstrated the possibility to inactivate bioaerosol containing S. epidermidis or Aspergillus niger , respectively, a Gram‐positive bacteria and fungal spores by means of CAP treatment. The morphology observed on the scanning electron microscope (SEM) micrographs shows deformations in the cellular structure of both microorganisms.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Romero‐Mangado et al [ 19 ] studied the effect of DBD on aerosolized E. coli concluding that the cell structure is damaged to a varying extent and severe oxidation of the cell membrane is found, establishing effective inactivation of the bacteria. Romero‐Mangado et al [ 29 ] also demonstrated the possibility to inactivate bioaerosol containing S. epidermidis or Aspergillus niger , respectively, a Gram‐positive bacteria and fungal spores by means of CAP treatment. The morphology observed on the scanning electron microscope (SEM) micrographs shows deformations in the cellular structure of both microorganisms.…”
Section: Introductionmentioning
confidence: 99%
“…Cell structure damage upon interaction with the DBD suggests leakage of vital cellular materials, which is a key mechanism for microbial inactivation. [ 29 ] Nayak et al [ 23 ] shows that a volumetric DBD is effective in inactivating aerosolized porcine reproductive and respiratory syndrome (PRRS) virus in a wind tunnel within a few milliseconds, timescales relevant for typical heating, ventilation, and air conditioning (HVAC) conditions (few milliseconds). A 3.5‐log reduction in the viable PRRS virus titer is achieved and the inactivation effect is independent of the discharge power and the sampling time.…”
Section: Introductionmentioning
confidence: 99%
“…Operating rooms with turbulent mechanical ventilation or without ventilation are not acceptable for orthopedic and traumatic surgery on COVID-19 patients. A safe technical solution is an innovative mobile filter system, which first sucks in room air through an M5 prefilter [26] , [27] . Then, the air passes through a G4 carbon pleated filter.…”
Section: Gas Plasma Technology and Decontaminationmentioning
confidence: 99%
“…Various types of plasma devices for these purposes were developed in recent years. The most widely studied and used plasma sources for bio-medical applications in various configurations and designs are based on the dielectric barrier discharge (DBD) and the atmospheric pressure plasma jets (APPJ) [13][14][15]. In [16], the plasma sources (assuming that the plasma is produced between electrodes) are categorized in three types: (i) direct plasma sources, when one of the electrodes is the sample (human body); (ii) indirect plasma sources, when the plasma is produced between two electrodes and the active plasma components are transported to the treated sample; and (iii) hybrid plasma sources-surface micro discharge (SMD) technology.…”
Section: Introductionmentioning
confidence: 99%